LGR5 is Expressed by Ewing Sarcoma and Potentiates Wnt/β-Catenin Signaling - Scannell, Christopher A.; Pedersen, Elisabeth A.; Mosher, Jack T.; Krook, Melanie A.; Nicholls, Lauren A.; Wilky, Breelyn A.; Loeb, David M.; Lawlor, Elizabeth R. (Frontiers in Oncology, 2013)
Ewing sarcoma (ES) is an aggressive bone and soft tissue tumor of putative stem cell origin that predominantly occurs in children and young adults. Although most patients with localized ES can be cured with intensive therapy, the clinical course is variable and up to one third of patients relapse following initial remission. Unfortunately, little is yet known about the biologic features that distinguish low-risk from high-risk disease or the mechanisms of ES disease progression. Recent reports have suggested that putative cancer stem cells exist in ES and may contribute to an aggressive phenotype. The cell surface receptor LGR5 (leucine-rich repeat-containing G-protein coupled receptor 5) is a somatic stem cell marker that functions as an oncogene in several human cancers, most notably colorectal carcinoma. LGR5 is a receptor for the R-spondin (RSPO) family of ligands and RSPO-mediated activation of LGR5 potentiates Wnt/β-catenin signaling, contributing to stem cell proliferation and self-renewal. Given its presumed stem cell origin, we investigated whether LGR5 contributes to ES pathogenesis. We found that LGR5 is expressed by ES and that its expression is relatively increased in cells and tumors that display a more aggressive phenotype. In particular, LGR5 expression was increased in putative cancer stem cells. We also found that neural crest-derived stem cells express LGR5, raising the possibility that expression of LGR5 may be a feature of ES cells of origin. LGR5-high ES cells showed nuclear localization of ß-catenin and robust activation of TCF-reporter activity when exposed to Wnt ligand and this was potentiated by RSPO. However, modulation of LGR5 or exposure to RSPO had no impact on proliferation confirming that Wnt/ β-catenin signaling in ES cells does not recapitulate signaling in epithelial cells. Together these studies show that the RSPO-LGR5-WNT- β-catenin axis is present and active in ES and may contribute to tumor pathogenesis.